2023
DOI: 10.1039/d3mh00483j
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-induced rapid gelation and mechanical reinforcement of hydrogels with low-hysteresis and self-recoverable and fatigue-resistant properties

Xingqi Luo,
Zhaoyang Yuan,
Xiangyan Xie
et al.

Abstract: Hydrogels with rapid gelation ability and robust mechanical properties are highly desirable for nascent applications in biomedical, wearable electronic, industrial and agricultural fields. However, current rapid-gelation hydrogels are compromised by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Upon correlating the measured mechanical strength with the microscopic as well as spectroscopic results of the coassembled hydrogels, it can be stated that the thinner and higher-ordered arrangement of fibers obtained from the heat–cool method induced fabrication of stiffer gels, whereas the flat and twisted arrangement of fibers obtained from the sonication method triggered the formation of weaker gels (Figure S5). It has also been reported that the presence of serine can provide additional hydrogen-bonding interactions which could further help in strengthening the mechanical properties of the coassembled system . In order to prove this, we have also evaluated the mechanical strength of only Cbz-FF-OH hydrogels formed through both heat–cool and sonication methods.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Upon correlating the measured mechanical strength with the microscopic as well as spectroscopic results of the coassembled hydrogels, it can be stated that the thinner and higher-ordered arrangement of fibers obtained from the heat–cool method induced fabrication of stiffer gels, whereas the flat and twisted arrangement of fibers obtained from the sonication method triggered the formation of weaker gels (Figure S5). It has also been reported that the presence of serine can provide additional hydrogen-bonding interactions which could further help in strengthening the mechanical properties of the coassembled system . In order to prove this, we have also evaluated the mechanical strength of only Cbz-FF-OH hydrogels formed through both heat–cool and sonication methods.…”
Section: Resultsmentioning
confidence: 90%
“…It has also been reported that the presence of serine can provide additional hydrogen-bonding interactions which could further help in strengthening the mechanical properties of the coassembled system. 79 In order to prove this, we have also evaluated the mechanical strength of only Cbz-FF-OH hydrogels formed through both heat−cool and sonication methods. Interestingly, upon comparing with the coassembled hydrogels, we observed a lower value of storage modulus for only Cbz-FF-OH hydrogels formed by both gelation pathways (Figure S4).…”
Section: Role Of Differential Self-assembling Pathways In Modulating ...mentioning
confidence: 99%
“…In our previous work, we discovered that amino acids were capable of activating the potassium persulfate (KPS)− tetramethylethylenediamine (TMEDA) initiating system, enabling efficient decomposition and the introduction of multiple hydrogen bonds, thereby achieving rapid gelation and mechanical reinforcement of free-radical polymerized hydrogels. 20 Based on this research, utilizing amino acids or their derivatives as an initiating-cross-linking agent is expected to fabricate injectable hydrogels with excellent mechanical properties under mild conditions. Apart from the necessary mechanical properties, an ideal injectable hydrogel for hemostasis and wound healing should possess excellent adhesive performance, hemostatic ability, antibacterial activity, and wound-healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this defect, the hybrid physically chemically cross-linked networks are introduced into the hydrogels to construct sufficient cross-linking sites among the macromolecules . The dynamic characteristics of multiple sacrificial bonds, such as hydrogen bonds and electrostatic interactions, confer the amphiphilic hydrogels with excellent elasticity and fatigue resistance . Presently, natural polysaccharides and their derivatives with abundant hydroxyl and carboxyl groups are anticipated to be adopted as hybrid physically chemically cross-linked networks for preparing high-performance hydrogels. Remarkably, curdlan, a natural polysaccharide with a unique stiff backbone of a triple-helical structure, exhibits interesting biological activities, gel properties, and abundant active hydroxyl groups conducive to forming dense dynamic hydrogen bonds and improving mechanical properties. Despite its potential versatile virtues, the application of curdlan is limited by its low solubility.…”
Section: Introductionmentioning
confidence: 99%
“…48 To resolve this defect, the hybrid physically chemically cross-linked networks are introduced into the hydrogels to construct sufficient crosslinking sites among the macromolecules. 49 The dynamic characteristics of multiple sacrificial bonds, such as hydrogen bonds and electrostatic interactions, confer the amphiphilic hydrogels with excellent elasticity and fatigue resistance. 50 Presently, natural polysaccharides and their derivatives with abundant hydroxyl and carboxyl groups are anticipated to be adopted as hybrid physically chemically cross-linked networks for preparing high-performance hydrogels.…”
Section: Introductionmentioning
confidence: 99%